2019
DOI: 10.1016/j.jfma.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

MiR-17-92 cluster and immunity

Abstract: MicroRNAs (MiR, MiRNA) are small single-stranded non-coding RNAs that play an important role in the regulation of gene expression. MircoRNAs exert their effect by binding to complementary nucleotide sequences of the targeted messenger RNA, thus forming an RNA-induced silencing complex. The mircoRNA-17-92 cluster encoded by the miR-17-92 host gene is first found in malignant B-cell lymphoma. Recent research identifies the miR-17-92 cluster as a crucial player in the development of the immune system, the heart, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…The miR-17-92 cluster, which is essential for the differentiation of immune cells, is highly expressed in EBV-positive tumors, such as NPC (41) and DLBCL (42). High expression of miR-17-92 in B cells, T cells, NK cells, macrophages, and dendritic cells is known to inhibit cellular differentiation and function (43).…”
Section: Host Mirna-mediated Evasion Of the Immune System By Ebv-infementioning
confidence: 99%
“…The miR-17-92 cluster, which is essential for the differentiation of immune cells, is highly expressed in EBV-positive tumors, such as NPC (41) and DLBCL (42). High expression of miR-17-92 in B cells, T cells, NK cells, macrophages, and dendritic cells is known to inhibit cellular differentiation and function (43).…”
Section: Host Mirna-mediated Evasion Of the Immune System By Ebv-infementioning
confidence: 99%
“…It also found that higher levels of miR‐17‐92 contribute to inhibition of tumor growth and metastasis in a mouse tumor model (Jiang et al, ). Recent research identified that the miR‐17‐92 cluster was a crucial player in the development of the immune system (Kuo, Wu, & Yang, ). Previous study indicated that MIR17HG copy numbers would seem to be related to response to neoadjuvant chemoradiotherapy in locally advanced rectal cancer (Molinari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the miR-17-92 cluster's increasing role in regulating the immune system is involved in innate and adaptive immunity, including B cells and subsets of T cells such as Th1, Th2, T follicular helper cells, regulatory T cells, monocytes/macrophages, NK cells, and dendritic cells [46]. Moreover, the study found that the miR-17 approximately 92 cluster is a critical regulator of T cell-dependent antibody responses and follicular helper T cells' (TFH cells) differentiation [47].…”
Section: T Cell Follicular Helper T Cells (Tfh Cells) and Th17mentioning
confidence: 99%
“…B cells play a critical role in immune responses, but the regulation of microRNAs to B-cell proliferation and function was partially understood. Not only miR-17-92 cluster was involved in B cell [46], but miR-146a also enhances class switch and secretion of IgE in B cells [53]. As an important immune regulatory cell, thrombospondin 1 (TSP1)-producing B cells were regulated by miRNAs as well.…”
Section: Mirna Regulates B Cellmentioning
confidence: 99%